Expression of the Receptor for Advanced Glycation End Products in Epicardial Fat: Link with Tissue Thickness and Local Insulin Resistance in Coronary Artery Disease - Elena Dozio; Elena Vianello; Silvia Briganti; John Lamont; Lorenza Tacchini; Gerd Schmitz; Massimiliano Marco Corsi Romanelli (Journal of Diabetes Research)
Increased expression of receptor for advanced glycation end products (RAGE) in adipose tissue has been associated with inflammation, adipocyte hypertrophy, and impaired insulin signal. Epicardial adipose tissue (EAT), a visceral fat surrounding the myocardium, is potentially involved in the onset/progression of coronary artery disease (CAD). To date, the role of RAGE in EAT has not been explored much. We examined whether the RAGE expression in EAT was associated with EAT adiposity and metabolic dysfunctions normally found in CAD patients. EAT samples were obtained from 33 patients undergoing open-heart surgery. EAT expression of RAGE, GLUT4, adiponenctin, GLO1, HMGB1, TLR-4, and MyD88 was analyzed by microarray. EAT thickness was quantified by echocardiography. Anthropometric measures and clinical parameters were taken. BMI, HOMA-IR, and LAP indices were calculated. With increasing RAGE expression in EAT we observed increases in EAT thickness, reduced expression of GLUT4, adiponectin, and GLO1, and elevations of HMGB1, TLR-4, and MyD88. There were significant correlations between RAGE and EAT thickness and between RAGE and the genes. LAP was higher in patients with increased RAGE expression. Our data suggest that in CAD patients RAGE may be involved in promoting EAT adiposity and metabolic dysfunction, such as impaired insulin signaling.